2007
DOI: 10.1186/1744-859x-6-29
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and therapeutic management of patients admitted to Italian acute hospital psychiatric units: the PERSEO (psychiatric emergency study and epidemiology) survey

Abstract: Background: The PERSEO study (psychiatric emergency study and epidemiology) is a naturalistic, observational clinical survey in Italian acute hospital psychiatric units, called SPDCs (Servizio Psichiatrico Diagnosi e Cura; in English, the psychiatric service for diagnosis and management). The aims of this paper are: (i) to describe the epidemiological and clinical characteristics of patients, including sociodemographic features, risk factors, life habits and psychiatric diagnoses; and (ii) to assess the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
8
5
0
Order By: Relevance
“…The mean age of our psychiatric sample is also in line with the mean age of general inpatient population reported in the Psychiatric Units in Italy [40]. The development of MetS in psychiatric patients at a younger age than in the internal medicine settings may also result from the presence of specific risk factors for MetS described only for the psychiatric population, such as the effect of the illness itself, food intake, energy expenditure, neuroendocrine dysregulation, and psychotropic medications [41].…”
Section: Discussionsupporting
confidence: 82%
“…The mean age of our psychiatric sample is also in line with the mean age of general inpatient population reported in the Psychiatric Units in Italy [40]. The development of MetS in psychiatric patients at a younger age than in the internal medicine settings may also result from the presence of specific risk factors for MetS described only for the psychiatric population, such as the effect of the illness itself, food intake, energy expenditure, neuroendocrine dysregulation, and psychotropic medications [41].…”
Section: Discussionsupporting
confidence: 82%
“…As a positive treatment response is usually defined in the literature as greater than 20% reduction in BPRS (Lachar et al, 1999), our findings showed that a short LOS in our ward was highly effective. Our results are consistent with previous systematic reviews (Alwan et al, 2008;Johnstone and Zolese, 2009) and the two Italian surveys (Ballerini et al, 2007a(Ballerini et al, , 2007bBarbato et al, 2010;Preti et al, 2009), suggesting that a short hospitalization is sufficient for the majority of patients (Frieri et al, 2013).…”
Section: Discussionsupporting
confidence: 95%
“…This proportion is substantially higher than previous reports on the prescription rate for atypical antipsychotics in Germany from Clade [6] and Haro [12] and higher than reports from some studies in other European countries. Nevertheless, Ballerini et al reported a prescription rate of 59 % for atypical antipsychotics at discharge in a study from Italy [3] . In Turkey, Atik et al reported that 75.1 % of patients were treated with atypical antipsychotics versus 24.9 % with typical antipsychotics.…”
Section: Methodsmentioning
confidence: 98%